Hubungan Frekuensi Coitus Dengan Persalinan Normal Di RS Asy Syifa Sambi Kabupaten Boyolali - Indarti Indarti; Sri Kustiyati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The success of the normal delivery process was influenced by many factors, including the frequency of coitus during pregnancy. Coitus or husbandand wife intercourse can improve blood circulation in the reproductive area, including the cervix, which helps soften and open the cervix, especially if it was often done during the third trimester of pregnancy. Coitus can also increase the production of the hormone oxytocin which can trigger uterine contractions and help speed up the normal delivery process. The objectives of the research: To analyzed the relationship between the frequency of coitus and the incidence of normal delivery. Method: This type of analytic research with correlational design and cross sectional approach. The sample used 84 people with purposive sampling. The instrument uses an observation sheet. Data analysis using chisquare. Result: The frequency of coitus the majority of respondents sometimes do (1-2x a week) (47,6%) and the majority of respondents are dominated by normal delivery (84,5%). The results of the chi square analysis obtained a chi square value of 62,786 > chi square table (5,99) with a significant value (p value) of 0,000 <0,05 so it can be interpreted that there is a relationship between thefrequency of coitus and the incidence of normal delivery. Conclusion: There wasa relationship between the frequency of coitus and normal delivery in the hospital.Asy Sifa Sambi, Boyolali Regency.